ANALYSIS OF STUDENTS’ COMPUTATIONAL THINKING ABILITY IN PRIOR MATHEMATICAL KNOWLEDGE - Angraini, Lilis Marina; Ilham Muhammad (Edupedia Publisher, 2023)
This research was motivated by the importance of Computational Thinking (CT) ability for students to get a better thinking and problem solving abilities. The purpose of the study describes the students' CT ability in terms of their Prior Mathematical Knowledge (PMK). The subjects of this study were 6 junior high school students consisting of 2 students who had a high prior mathematical knowledge, 2 students who had a medium prior mathematical knowledge, and 2 students who had a low prior mathematical knowledge. The selection of subjects was not randomly selected. The method of research used was descriptive qualitative, where the data presented were deepened by interviews. Furthermore, the instruments used were test and non-test. In this case, the CT test was used to determine students' CT ability in terms of their prior mathematical knowledge, while the non-test in the form of interviews was used to find out the reasons for their test answers. The results of this study indicate that students who had a high prior mathematical knowledge were able to meet the CT mathematical indicators well. Furthermore, students who had a medium prior mathematical knowledge were able to meet several mathematical CT indicators, while students who had a low prior mathematical knowledge cannot fulfill mathematical CT indicators well.